The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.1002/casp.2559
|View full text |Cite
|
Sign up to set email alerts
|

The mediating role of national identification, binding foundations and perceived threat on the relationship between need for cognitive closure and prejudice against migrants in Malta

Abstract: What mitigates the relationship between need for cognitive closure and prejudice against migrants? Addressing this question, we explored how national identification, endorsing binding moral foundations and the perception of threat mediate the relationship between need for cognitive closure and prejudice against migrants in Malta. It was hypothesized that individuals with a high need for cognitive closure are more prone to identify with being Maltese and more probable to endorse binding moral foundations and pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
2
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 71 publications
(83 reference statements)
1
2
0
1
Order By: Relevance
“…The results confirmed that the higher the NFC, the stronger the prejudice, in line with H1. This hypothesis was confirmed in line with findings reported in the literature (e.g., Bianco et al, 2021;. Indeed, high NFC individuals tend to attach particular importance to the in-group, devaluing the out-group.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…The results confirmed that the higher the NFC, the stronger the prejudice, in line with H1. This hypothesis was confirmed in line with findings reported in the literature (e.g., Bianco et al, 2021;. Indeed, high NFC individuals tend to attach particular importance to the in-group, devaluing the out-group.…”
Section: Discussionsupporting
confidence: 91%
“…For example, high NFC is associated with a heuristic and top-down elaboration of information and may push an individual to overuse biases, easily accessible stereotypes, and pre-existing attitudes (Kossowska et al, 2015, 2018; Kruglanski & Webster, 1996; Perry & Sibley, 2013; Shah et al, 1998; Theodorou & Livi, 2021). Several studies demonstrated that the NFC is associated with in-group bias and out-group derogation (Golec & Federico, 2004; Kruglanski et al, 2002; Kruglanski & Webster, 1996; Roets et al, 2015; Shah et al, 1998), and with the prejudice against minority groups (Baldner et al, 2019; Baldner & Pierro, 2019; Bianco et al, 2021; Roets & van Hiel, 2011).…”
Section: The Need For Closure (Nfc) and Prejudicementioning
confidence: 99%
“…Threat of nuclear war had been added to this during the Cold War (see Lebovic, 2009;Mayton II, 1986;Schatz, & Fiske, 1992). However, recently, for many societies, threat perceptions moved from the Cold War mentality towards terrorism (Goodwin, Willson, & Stanley Jr, 2005;Leventhal, & Chellaney, 1988;Malhotra & Popp, 2012;Nissen et al, 2015;Pelletier, & Drozda-Senkowska, 2016;Stevens et al, 2011), foreigners (Watts, 1996), minorities (Canetti-Nisim, Ariely, & Halperin, 2008;Tahir, Kunst, & Sam, 2019;Verkuyten, 2009), refugees (Thomsen, & Rafiqi, 2020), immigrants and/or immigration (Araújo et al, 2019;Badea, Bender, & Korda, 2020;Ben-Nun Bloom, Arikan, & Lahav, 2015;Bianco, Kosic, & Pierro, 2022;Blinder, & Lundgren, 2019;Canetti et al, 2016;Erisen, & Kentmen-Cin, 2017;Escandell, & Ceobanu, 2009;Ha & Jang, 2015;Kiehne, & Cadenas, 2021;Kustov, 2019;Larsen et al, 2009;McLaren, 2003;Paxton & Mughan, 2006;Pereira, Vala, & Costa-Lopes, 2010;Thomsen, & Rafiqi, 2020;Vala, Pereira, & Ramos, 2006;Woods, & Marciniak, 2017), climate change (Carmi & Kimhi, 2015;Davydova et al, 2018;Schwaller et al, 2020), disasters…”
Section: The Political Psychology Of Threat Perceptionsmentioning
confidence: 99%
“…Moreover, NI was associated with negative attitudes towards foreign immigrants, refugees, asylum seekers in France (Adam‐Troian et al, 2019), Australia (Anderson & Ferguson, 2018), Malta (Bianco et al, 2022), Switzerland (Dierckx et al, 2022) and Turkey (Yitmen & Verkuyten, 2018). At the same time, GHI was associated with support for human rights (McFarland, 2010, 2015, 2017; McFarland & Hornsby, 2015; Reysen et al, 2013) and positive attitudes towards ethnic and religious outgroup members (McFarland et al, 2019).…”
Section: Introductionmentioning
confidence: 99%